Measuring environmental strategy : construct development, reliability, and validity - Berrone, Pascual (2013)
Inconsistent results in prior work that link environmental strategy to competitive advantage may be due to the empirical difficulties of marrying the theoretical connection between a firm’s resource base and its environmental strategy. The authors contribute to the field by developing a measure that is congruent with the natural resource—based view, a dominant paradigm in this line of work. This article content analyses company reports and secondary data to develop a measure of environmental strategy grounded in the natural resource—based view. They identify six environmental capabilities that form components of a reliable, multidimensional construct of proactive environmental strategy. They also identify a measure of reactive compliance strategy. They verify reliability of their new measure through exploratory and confirmatory factor analyses, establish convergent and discriminant validity via a multitrait, multimethod matrix and demonstrate superior predictive validity of their measure compared to two others commonly used in the literature. In the conclusion, they discuss implications for research and practice.